Biomimetic whitlockite inorganic nanoparticles-mediated in situ remodeling and rapid bone regeneration. (January 2017) - Kim, Hwan D.; Jang, Hae Lin; Ahn, Hyo-Yong; Lee, Hye Kyoung; Park, Jungha; Lee, Eun-seo; Lee, Eunjee A.; Jeong, Yong-Hoon; Kim, Do-Gyoon; Nam, Ki Tae; Hwang, Nathaniel S.
Abstract: Bone remodeling process relies on complex signaling pathway between osteoblasts and osteoclasts and control mechanisms to achieve homeostasis of their growth and differentiation. Despite previous achievements in understanding complicated signaling pathways between cells and bone extracellular matrices during bone remodeling process, a role of local ionic concentration remains to be elucidated. Here, we demonstrate that synthetic whitlockite (WH: Ca18 Mg2 (HPO4 )2 (PO4 )12 ) nanoparticles can recapitulate early-stage of bone regeneration through stimulating osteogenic differentiation, prohibiting osteoclastic activity, and transforming into mechanically enhanced hydroxyapatite (HAP)-neo bone tissues by continuous supply of PO4 3− and Mg 2+ under physiological conditions. In addition, based on their structural analysis, the dynamic phase transformation from WH into HAP contributed as a key factor for rapid bone regeneration with denser hierarchical neo-bone structure. Our findings suggest a groundbreaking concept of 'living bone minerals' that actively communicate with the surrounding system to induce self-healing, while previous notions about bone minerals have been limited to passive products of cellular mineralization.